Stability Ball Sitting Elevates Peak Arm Ergometry Oxygen Consumption and Heart Rate - MARKS, CHARLES R.C. (Int J Exerc Sci, 2012)
This study compared sitting on a stability ball (B) to sitting on a chair (C) during arm ergometry to determine the impact on peak VO(2), peak heart rate (HR), and exercise intensity prescription. Open-circuit spirometer, blood pressure, and HR were monitored during rest and continuous graded exercise test to exhaustion using an arm ergometer. Twenty-seven apparently healthy adults exercised twice, once at B and the other trial C (order randomized), with 60 minutes of rest between trials. ANOVA for repeated measures (α < 0.05) and paired t testing using Holm’s-sequential Bonferroni were used to analyze results for 30 W, 45 W, Penultimate, and Peak stages of exercise. VO(2) was significantly higher (8% to 12%, P < 0.001) for all stages of exercise for B compared to C. HR was significantly higher (P < 0.001) only at the Penultimate and Peak levels (3% and 2%, respectively) for B compared to C; all other sub-maximal HRs were not significantly different. There were no significant main effects or interactions (P≥ 0.138) when VO(2) and HR were expressed as percentage of maximum. Compared to chair sitting, the stability ball has a greater absolute metabolic response with little impact on HR. Prescribing exercise with absolute MET levels should consider this; however, intensity as a percentage of maximum may not be affected by the stability ball.